Virtual Tours of Museums to Promote Tourism - Cóndor-Herrera, Omar (2023)
Museums represent a collection of ancient and modern knowledge which must be protected, disseminated, and transmitted in the best viable way. Digital development and technology in recent years have made it possible to transform the way of interacting with museums through virtual tours (Palmieri et al in Springer Series in Design and Innovation, pp 71–82, 2023 [1]), which gained strength in times of pandemic, the products generated for virtual tours range from physical reproductions/faithful virtual images of historical artifacts to digital libraries that can be used by experts and others, in addition to 360º technology which allows a 360° viewing angle to be covered in two axes. That is, we can see everything around the point where it was made the photo or video. In this article, the virtual tours offered by some museums are analyzed, as well as the use of these tours as a tourism marketing strategy, giving the user the opportunity to interact with the place they plan to visit in a new way (Cóndor-Herrera and Ramos-Galarza in Marketing and smart technologies. Smart innovation, systems and technologies, pp 443–449, 2022 [2])